ETHANOL IN BRAZIL: A PREDICTIVE PRICING APPROACH - de Brito, Fabrício Bisset Silva; Santos, Leandro Brito; Monteiro, Roberto Luiz Souza; Guedes, Everaldo Freitas (Seven Editora, 2025)
The production of liquid biofuels has emerged as an alternative to the use of fossil fuels for transportation purposes. Ethanol is described as a renewable energy fuel. In 2021, Brazil produced 27.46% of the world’s ethanol, ranking second among producing countries. The introduction of light commercial and passenger vehicles with Flex Fuel technology, which uses both Type C gasoline and hydrous ethanol, into the Brazilian market, began in March 2003, significantly impacting ethanol demand in the Brazilian consumer market. This study aims to compare the predictive accuracy of the ARFIMA, ARIMA, and Smoothed Exponential models for Brazilian ethanol prices over a four-year period. DOI: https://doi.org/10.56238/sevened2025.029-058